(untitled) (Academic journal Industrial Machine Building Civil Engineering, 2018)
A method for reducing the uneven deformations of a two-story building, which provides improving the construction properties of weak soils that lie at the base, by reinforcing them with horizontal soil-cement elements (SCE) of increased rigidity, carried out using a sand mixing technology, is described. SCEs are created in the mass under the base of the foundations and are formed as a result of the destruction of soil natural structure with its simultaneous mixing and injection of cement mortar under pressure. It has been established that the manufacture of SCE has a number of advantages: using of local soil as a material for their manufacture; adding to the soil only water and a binder, without additional aggregate; installation of elements on the site.